Family sports interventions for the treatment of obesity in childhood: a meta-analysis - Lihong Yang; Chao Liang; Yaona Yu; Qian Xiao; Maomao Xi; Lixu Tang (BMC, 2022)
Abstract Background Obesity in children has become one of the key concerns of the World Health Organization, and the incidence of related non-communicable diseases is also rising. This study evaluates the effect of family sports participation on the treatment and prevention of obesity in children aged 0-14 years by systematic analysis. Method A literature review from 2000 to 2020 was conducted. According to PRISMA-IPD (Preferred Reporting Items for MetaAnalyses of individual participant data) guidelines. The two researchers independently assessed the risk and bias of the articles, obtained a comprehensive, high-quality result, and extracted the data based on the Cochrane intervention system review manual. Randomized controlled trials (RCTs) were selected from the searches that used family sports interventions or family sports combined with dietary adjustments and behavioral habits change. Only studies targeting overweight or obese children aged 0-14 years were included. Results The search resulted in a total of 16 studies. Across all 16 studies, there were a total of 1680 participants in the experimental groups and 1701 participants in the control groups. The results are as follows: body mass index (BMI) (SMD-RE = − 4.10, 95% CI (− 0.84 to 0.02), Z = 1.88, p = 0.06); Body weight (SMD-RE = − 0.77, 95% CI (− 1.53 to − 0.01), Z = 2.00, p = 0.05); Waist circumference (SMD-RE = − 0.45, 95% CI (− 1.36 to 0.47), Z = 0.96, p = 0.34); and Body fat rate (SMD-FE = − 0.06, 95% CI (− 0.22 to 0.11), Z = 0.69, p = 0.49). Hence, through family sports intervention among obese children, juvenile and obese body composition-BMI, body weight, waist circumference, and body fat rate-are all reduced. But only body weight was statistically significant. Conclusions Compared with the samples without family sports, the weight of obese children participating in family sports decreased, but there were no significant differences in other relevant physical indicators. Follow-up research should examine large-scale clinical trials with family sports as a single factor intervention, which are needed to provide stronger evidence of the intervention effect. However, family activities can help obese children grow and develop by improving their exercise capacity, enhancing their lifestyles, and facilitating communication and relationships with their parents. In the future, long-term sports training plans for children with obesity should be implemented.